Treatment of atypical hemolytic uremic syndrome with eculizumab in a patient presenting with neuropsychiatric prodrome: a case report - Yang, Hanze; Zhang, Jingdong; Wu, Hao; Xu, Hongzhao; Xu, Zhonggao (Frontiers in Immunology, 2025)
Atypical hemolytic uremic syndrome (aHUS) is a rare thrombotic microangiopathy (TMA) caused by dysregulation of the complement system. It is characterized by microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury. Owing to its diverse and nonspecific clinical manifestations, early diagnosis of the condition is challenging and typically requires excluding other TMA-related conditions, such as thrombotic thrombocytopenic purpura and hemolytic uremic syndrome caused by Escherichia coli infection. Accurate diagnosis relies on the recognition of typical TMA symptoms, laboratory testing, and the exclusion of other conditions. Treatments typically include plasma exchange, supportive care, and complement-targeted therapy. Eculizumab, a complement component 5 inhibitor, plays a crucial role in aHUS treatment in severe cases as well as when traditional interventions fail. In this case report, we described a female Han Chinese patient who developed aHUS following an upper respiratory tract infection, initially presented with intermittent seizures, and received treatment with eculizumab, plasma exchange, and hemodialysis. The patient ultimately remained dialysis-dependent; however, they achieved complete remission for other systemic complications of aHUS. We emphasized in this case report the importance of timely diagnosis and treatment of aHUS as well as the potential value of eculizumab in improving patient outcomes. Furthermore, successful treatment and follow-up results provide insights into the management of this rare disease, including long-term dialysis requirements and disease monitoring after remission. Thus, clinicians can better understand the clinical manifestations of aHUS and its associated diagnostic challenges, treatment strategies, and long-term management needs.